Book examines outsourcing pros and cons. (American City & County, 2000)
A review of the book “Privatization and Public-Private Partnerships” by E. S. Savas is presented. The author examines the changing face of privatization, the advantages and disadvantages of outsourcing, and the elements that have influenced privatization from the beginning.